2020
DOI: 10.1177/0363546520968566
|View full text |Cite
|
Sign up to set email alerts
|

Medial Patellofemoral Ligament Reconstruction With or Without Derotational Distal Femoral Osteotomy in Treating Recurrent Patellar Dislocation With Increased Femoral Anteversion: A Retrospective Comparative Study

Abstract: Background: Controversy exists regarding the surgical treatment of recurrent patellar dislocation (RPD) with an increased femoral anteversion angle (FAA). Medial patellofemoral ligament reconstruction (MPFL-R) either alone or combined with derotational distal femoral osteotomy (DDFO) results in favorable clinical outcomes. Purpose: To compare the clinical outcomes of MPFL-R versus MPFL-R with DDFO in treating RPD with increased FAA (>30°). Study Design: Cohort study; Level of evidence, 3. Methods: Between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(84 citation statements)
references
References 32 publications
(68 reference statements)
0
84
0
Order By: Relevance
“…Due to these abnormal biomechanics of osseous deformity, it is vital to identify these underlying predisposing risk factors and to early make intervention for RPD. Despite isolated anatomical MPFL reconstruction is considered to be a standard treatment for patellofemoral instability with satisfactory results [ 31 , 32 ], subsequent studies have demonstrated that a high rate of subjective dissatisfaction in patients with increased femoral internal torsion [ 33 ]. Supracondylar FDO as an isolated procedure has been shown good clinical outcomes for RPD with increased FAA [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to these abnormal biomechanics of osseous deformity, it is vital to identify these underlying predisposing risk factors and to early make intervention for RPD. Despite isolated anatomical MPFL reconstruction is considered to be a standard treatment for patellofemoral instability with satisfactory results [ 31 , 32 ], subsequent studies have demonstrated that a high rate of subjective dissatisfaction in patients with increased femoral internal torsion [ 33 ]. Supracondylar FDO as an isolated procedure has been shown good clinical outcomes for RPD with increased FAA [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical basis of the increased risk likely lies with an increase in the Q angle resulting from the femoral anteversion, which exerts laterally directed forces on the patella. For this reason, in recent years, there have been some reports of femoral derotation osteotomy in addition to MPFL reconstruction as a treatment for recurrent patellar dislocation to decrease femoral anteversion [13]. In the present case, the increased FAA was corrected from 44°to 27°by THA combined with subcutaneous adductor tenotomy.…”
Section: Discussionmentioning
confidence: 57%
“…Due to these abnormal biomechanics of osseous deformity, it is vital to identify these underlying predisposing risk factors and to early make intervention for RPD. Despite isolated anatomical MPFL reconstruction is considered to be a standard treatment for patellofemoral instability with satisfactory results [23,24], subsequent studies have demonstrated that a high rate of subjective dissatisfaction in patients with increased femoral internal torsion [25]. Supracondylar femoral derotation osteotomy as an isolated procedure has been shown good clinical outcomes for RPD with increased FAA [26,27].…”
Section: Discussionmentioning
confidence: 99%